Tingkat kepuasan pasien peserta JKN terhadap kualitas pelayanan kesehatan gigi dan mulut di Poliklinik Gigi Puskesmas 1 Denpasar Timur - Ida Ayu Indira Sarasija; Steffano Aditya Handoko; Ni Made Sri Nopiyani (School of Dentistry Faculty of Medicine Udayana University, 2018)
Background: Puskesmas I Denpasar Timur has the third highest patient visits in Denpasar, and the majority of the patient visits in Dental Care Unit are JKN patients. This condition should be conducted with good quality of oral health care and the quality can be assessed through patient satisfaction. Objective: The objective of this study is to determine the satisfaction level among JKN participant’s patients toward dental and oral health care in Dental Care Unit of Puskesmas I Denpasar Timur. Methods: This study was using a descriptive quantitative with cross-sectional design and a consecutive sampling was conducted on 97 patients. Data were obtained through questionnaires developed from the Donabedian service quality framework, and the results of the study were analyzed using univariate method. Results: The results of this study showed that 77,3% of the patient are satisfied with oral health care in Dental Care Unit of Puskesmas I Denpasar Timur. 92,8% of JKN patients were satisfied with healthcare structure variable and 75,3% JKN patients were satisfied with healthcare process variable. Conclusions: Based on the results of this study, the majority of JKN patients are satisfied with oral health care in Puskesmas I Denpasar Timur, but the management of Puskesmas I Denpasar Timur still needs some improvement on the quality of dental and oral healthcare especially for the interaction aspect between health workers and patients.